The Implementation of Meaningful Learning in Enhancing Conceptual Understanding of Fifth-Grade Students in Mathematics - Pahruroji; Suriswo; Basukiyatno (South Sulawesi Education Development (SSED), 2025)
This study aims to analyze the implementation of meaningful learning in improving fifth-grade students' conceptual understanding of mathematics at Dabin Werkudara Elementary School, Bumijawa District, Tegal Regency. The research approach used was a qualitative case study method involving five elementary schools: Dukuhbenda 01 Elementary School, Dukuhbenda 02 Elementary School, Dukuhbenda 04 Elementary School, Muncanglarang 02 Elementary School, and Sigedong 02 Elementary School. Data were collected through in-depth interviews with teachers and students, as well as direct observation during the learning process. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that meaningful learning helps students connect mathematical concepts with real-world experiences, thereby enhancing conceptual understanding and learning motivation. Teachers play a crucial role in creating a contextual learning environment through the use of concrete media, discussions, and collaborative activities.